Social Support and Health in Italy: The Impact of the Disease During the COVID-19 Pandemic - Lonardi, Cristina; Tronca, Luigi (Italian Sociological Review, 2025)
The COVID-19 pandemic has put a strain on formal and informal support and care networks, which have had to draw on their reserves of social capital to deal with the health emergency. As part of a national research project on “Social capital as resource of care practice in Italy: Caregiving and social support in pandemic time”, this research aimed to monitor the dynamics related to the mechanisms that lead individuals to provide support, to the point of assuming, where appropriate, the role of caregiver. This article presents the results of qualitative research that focused on the personal support networks of persons who have contracted COVID-19 and persons who have faced a chronic/chronic degenerative disease during the pandemic period. The study reveals a scenario in which, despite the health emergency and general restrictions on social relations, social support relationships have not been lost, and individuals have relied on their social resources, i.e., social support in its various relational dimensions. Furthermore, it clearly emerged that residential proximity contexts have expanded individuals’ ability to take on the role of mediators in their personal support networks and, in this way, to develop them significantly. Expanding the support network, guaranteed by mediation, has led to a greater sense of well-being.